Machines : a visual history : 100 machines and the remarkable stories behind each invention - Chinea, Dominic (Dorling Kindersley Limited, 2024)
"Filled with stunning illustrations and lively, engaging text, The Repair Shop's Dom Chinea guides readers through this celebration of the history and uses of 100 machines that have allowed artisans to create beautiful items for centuries. Fans of prime-time TV shows The Repair Shop and Make It at Market will not want to miss Dom's insightful and complete appraisal of history's most game-changing mechanisms, with commentary that allows readers to get under the hood of inventions that have defined modern life as we know it"--publisher.